2015
DOI: 10.1186/s40249-015-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Malaria endemicity and co-infection with tissue-dwelling parasites in Sub-Saharan Africa: a review

Abstract: Mechanisms and outcomes of host-parasite interactions during malaria co-infections with gastrointestinal helminths are reasonably understood. In contrast, very little is known about such mechanisms in cases of malaria co-infections with tissue-dwelling parasites. This is lack of knowledge is exacerbated by misdiagnosis, lack of pathognomonic clinical signs and the chronic nature of tissue-dwelling helminthic infections. A good understanding of the implications of tissue-dwelling parasitic co-infections with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 178 publications
0
20
0
Order By: Relevance
“…Recently, outbreaks of trichinellosis also occurred in the mountainous regions of Cambodia, Lao PDR, north Thailand and Vietnam, and most of the patients had consumed traditional raw or undercooked pork dishes at wedding, funeral, or New Year parties [ 7 10 ]. Trichinellosis has become an emerging and re-emerging zoonotic disease with health, social, and economic impacts in developing countries [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, outbreaks of trichinellosis also occurred in the mountainous regions of Cambodia, Lao PDR, north Thailand and Vietnam, and most of the patients had consumed traditional raw or undercooked pork dishes at wedding, funeral, or New Year parties [ 7 10 ]. Trichinellosis has become an emerging and re-emerging zoonotic disease with health, social, and economic impacts in developing countries [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have implicated cerebral malaria (Sowunmi, 1993;Vanni et al, 1998;Ekram et al, 2016;Singh et al, 2016;Jenkins et al, 2019) and toxoplasmosis (James et al, 2013;Yolken et al, 2017;Lindgren et al, 2018;Wokem and Onosakponome, 2018) in psychosis. Malaria parasites and T. gondii share similarities in their pathology, energy metabolism and immune modulation (Onkoba et al, 2015). The concomitant occurrence of the two pathogens in a human host may imply a competitive interaction that may modulate the clinical outcomes associated with the two diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the same gene, inner membrane complex, in P. berghei and T. gondii showed that 33% were similar [9,10]. T. gondii and Plasmodium parasites have been documented to share similar traits, especially with respect to biochemical and molecular pathways involved in pathology, immunomodulation, and metabolism [11]. This may indicate that parasites during co-infection can result in a competitive establishment that can promote or inhibit parasitological pathogenesis and fetal and birth outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that parasites during co-infection can result in a competitive establishment that can promote or inhibit parasitological pathogenesis and fetal and birth outcomes. Yet, the disease outcome and immunological response induction as a consequence of interaction between Plasmodium and T. gondii remain largely elusive [11]. In this study, we determined the resistance to T. gondii (ME49) in mice induced by malaria P. berghei (ANKA) infection.…”
Section: Introductionmentioning
confidence: 99%